Treg in inborn errors of immunity: gaps, knowns and future perspectives - Rebeca Kennedy-Batalla; Daniel Acevedo; Yiyi Luo; Ana Esteve‐Solé; Alexandru Vlagea; Rafael Correa‐Rocha; Ma Elena Seoane-Reula; Laia Alsina (2024)
Regulatory T cells (Treg) are essential for immune balance, preventing overreactive responses and autoimmunity. Although traditionally characterized as CD4+CD25+CD127 low FoxP3 hi , recent research has revealed diverse Treg subsets such as Tr1, Tr1-like, and CD8 Treg. Treg dysfunction leads to severe autoimmune diseases and immune-mediated inflammatory disorders. Inborn errors of immunity (IEI) are a group of disorders that affect correct functioning of the immune system. IEI include Tregopathies caused by genetic mutations affecting Treg development or function. In addition, Treg dysfunction is also observed in other IEIs, whose underlying mechanisms are largely unknown, thus requiring further research. This review provides a comprehensive overview and discussion of Treg in IEI focused on: A) advances and controversies in the evaluation of Treg extended subphenotypes and function; B) current knowledge and gaps in Treg disturbances in Tregopathies and other IEI including Treg subpopulation changes, genotype-phenotype correlation, Treg changes with disease activity, and available therapies, and C) the potential of Treg cell-based therapies for IEI with immune dysregulation. The aim is to improve both the diagnostic and the therapeutic approaches to IEI when there is involvement of Treg. We performed a non-systematic targeted literature review with a knowledgeable selection of current, high-quality original and review articles on Treg and IEI available since 2003 (with 58% of the articles within the last 6 years) in the PubMed database.